2015
DOI: 10.1021/acssynbio.5b00038
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Based Engineering of Actinomycetal Genomes

Abstract: Bacteria of the order Actinomycetales are one of the most important sources of pharmacologically active and industrially relevant secondary metabolites. Unfortunately, many of them are still recalcitrant to genetic manipulation, which is a bottleneck for systematic metabolic engineering. To facilitate the genetic manipulation of actinomycetes, we developed a highly efficient CRISPR-Cas9 system to delete gene(s) or gene cluster(s), implement precise gene replacements, and reversibly control gene expression in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
328
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 380 publications
(371 citation statements)
references
References 58 publications
8
328
3
5
Order By: Relevance
“…Due to the lack of technology to freely engineer this species, discovery of novel drugs or enhancing the production of already produced natural products has been hampered from further development. However, along with the advances in the genetic tools for Streptomyces species engineering such as the recently enabled CRISPR for actinomycetes, [243] the prospect with which these native producers hold is bright. [5,244] Then, E. coli itself also has a large room to be developed further as a prominent heterologous host for polyketide biosynthesis.…”
Section: Perspectivesmentioning
confidence: 99%
“…Due to the lack of technology to freely engineer this species, discovery of novel drugs or enhancing the production of already produced natural products has been hampered from further development. However, along with the advances in the genetic tools for Streptomyces species engineering such as the recently enabled CRISPR for actinomycetes, [243] the prospect with which these native producers hold is bright. [5,244] Then, E. coli itself also has a large room to be developed further as a prominent heterologous host for polyketide biosynthesis.…”
Section: Perspectivesmentioning
confidence: 99%
“…However, efficiency and specificity are greatly improved if a homology template for HR is provided. [45][46][47] This has been demonstrated in independent studies, in which Cobb et al [45] and Huang et al [46] reported 60%100% and 70%100% efficiencies, respectively, whereas Tong et al [47] reported near 100% efficiency for their studies on the actinorhodin gene cluster in S. coelicolor.…”
Section: Molecular Tools For Streptomycetes Engineeringmentioning
confidence: 97%
“…The CRISPR-Cas9 technique can be applied for deletion of genes and gene clusters [45][46][47] in a multiplex manner, [45] reversible gene expression control, [47] and induction. [48] The optimized system relies on two components: the single guide RNA (sgRNA), which is a synthetic RNA consisting of a CRISPR RNA (crRNA) and transactivating crRNA (tracrRNA) complex, and is required for guiding Cas9 to modify the targeted genome sequence; and the endonuclease Cas9 or catalytically inactive dCas9, which upon interaction with the sgRNA, scans the genome for protospacer adjacent motif (PAM) sequences and the corresponding 20 bp recognition site.…”
Section: Molecular Tools For Streptomycetes Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many Actinomycetales species are recalcitrant to genetic manipulation, a fact that has severely hampered their use for metabolic engineering. CRISPRCas9 has been used to inactivate multiple genes in actinomycetes (Tong et al 2015), indicating its ability to enable the creation of designer bacterial strains with enhanced metabolite production capabilities. CRISPR has also facilitated multiplexed metabolic pathway engineering in yeast at high efficiencies (Jakociunas et al 2015a,b), as well as random mutagenesis of yeast chromosomal DNA for phenotypic screening of desired mutants (Ryan et al 2014).…”
Section: Synthetic Biology and Genome-scale Engineeringmentioning
confidence: 99%